Inhibition of TLR1/2 dimerization by enantiomers of metal complexes. Issue 83 (9th September 2016) - Liu, Li-Juan; Wang, Wanhe; Zhong, Zhangfeng; Lin, Sheng; Lu, Lihua; Wang, Yi-Tao; Ma, Dik-Lung; Leung, Chung-Hang
Abstract : Complex1 and its enantiomerΛ-1 are reported for the first time to inhibit NF-κB transduction via the modulation of Pam3 CSK4 -induced TLR1/2 heterodimerization. Abstract : We report herein the identification of an immunomodulatory metal-based complex1 as a direct inhibitor of TLR1/2 heterodimerization. Both enantiomers of complex1 selectively suppressed TNF-α and TLR1/2 heterodimerization in Pam3 CSK4 -induced macrophages, withΛ-1 being more potent thanΔ-1 . Moreover, the complexes inhibited NF-κB transduction via the modulation of TLR1/2 signaling. To our knowledge, complex1 is the first metal-based inhibitor of TLR1/2 heterodimerization reported to date.